Hours of Opportunity, Volume 2 The Power of Data to Improve After-School Programs Citywide - McCombs, Jennifer Sloan (RAND Corporation, 2010)
The Wallace Foundation sponsored an initiative to help five cities increase collaboration, access, quality, information sharing, and sustainability in their out-of-school-time systems. The second in this three-volume series describes how Wallace Foundation grantees and three other cities used management information systems to collect and use data on out-of-school-time programs, including enrollment, attendance, and student outcomes.